Polyhedral oligomeric silsesquioxane polyimide nanocomposites for color filters and flexible conductive films. Issue 19 (11th December 2020) - Qian, Min; Zhou, Bo; Liu, Gang; Gao, Yang; Niu, Yueping; Gong, Shangqing
Abstract: Color filters and conductive films are widely used in spacecraft, while the lack of lightweight, flexibility, and atomic oxygen (AO) durability confine their potential applications in low earth orbit. In this study, a clear poly(amic acid) with an empirical 20 wt% polyhedral oligomeric silsesquioxane (POSS) solid content is designed for transparency and AO durability. Red, green, blue, and yellow dyes are reinforced with small amounts of 1–5 wt% in POSS polyimides for color filters. A silver nanowire network film is infiltrated onto the POSS polyimide for conductive film. Erosion depth upon hyperthermal AO exposure, surface morphology, surface chemistry, optical transparency, and conductivity have been systematically investigated. The erosion yields of all 20 wt% POSS polyimides decrease by an order of magnitude when subjected to 2.32 ± 0.05 and 2.39 ± 0.06 × 10 20  atoms cm −2 AO fluences, as passivating SiOx networks are formed on film surface. The small‐amount dye additives into polyimides do not introduce obvious changes in AO durability and surface chemistry. The silver nanowire infiltrated POSS polyimide film shows a 65.7% transmittance at 550 nm and a sheet resistance of 8.50 ± 0.36 Ohm square −1 . This study reveals promising attempts of POSS‐polyimide‐based color filters and flexible conductive films for potential space applications. Abstract : A clear polyimide with 20 wt% POSS solid content is designed for transparency and AO durability. Red, green, blue, and yellow dyes are reinforced in POSS polyimides with small amounts of 1‐5 wt% for color filters. A silver nanowire network film is infiltrated onto the POSS polyimide for conductive film.